Memory expression is independent of memory labilization/reconsolidation - Barreiro, Karina Andrea (2013)
There is growing evidence that certain reactivation conditions restrict the onset of both the destabilization phase and the restabilization process or reconsolidation. However, it is not yet clear how changes in memory expression during the retrieval experience can influence the emergence of the labilization/reconsolidation process. To address this issue, we used the context-signal memory model of Chasmagnathus. In this paradigm a short reminder that does not include reinforcement allows us to evaluate memory labilization and reconsolidation, whereas a short but reinforced reminder restricts the onset of such a process. The current study investigated the effects of the glutamate antagonists, APV (0.6 or 1.5 μg/g) and CNQX (1 μg/g), prior to the reminder session on both behavioral expression and the reconsolidation process. Under conditions where the reminder does not initiate the labilization/reconsolidation process, APV prevented memory expression without affecting long-term memory retention. In contrast, APV induced amnesic effects in the long-term when administered before a reminder session that triggers reconsolidation. Under the present parametric conditions, the administration of CNQX prior to the reminder that allows memory to enter reconsolidation impairs this process without disrupting memory expression. Overall, the present findings suggest that memory reactivation – but not memory expression- is necessary for labilization and reconsolidation. Retrieval and memory expression therefore appear not to be interchangeable concepts.